OUTCOME OF THE DISTAL RADIUS FRACTURES MANAGED WITH ACROSS WRIST EXTERNAL FIXATOR VS BUTTRESS PLATE - Ali, Rehman; Anis Ilyas,; Hizbullah Riaz,; Umar Faheem,; Junaid Khan,; Naeem Ahmed,; Amir Aziz, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Distal radius fracture is one of the most common injuries presented to emergency department and can be presented in any age group. In young patients the most common cause is Road Traffic Accident (RTA), while old patient history of fall is the most common cause. Different surgical options are available to treat this injury. This study aims to compare the outcome of volar buttress plate vs across wrist external fixator for Arbeitsgemeinschaft fÃ¼r Osteosynthesefragen (AO) type C2/C3 fracture of the distal radius. Methods: A retrospective comparative study between July 2020 to June 2021 at Ghurki Trust Teaching Hospital was done and a total of 50 patients who underwent surgical intervention for AO C2/C3 fracture of the distal Radius, were included. The follow-up period was 12 weeks. QuickDASH score was used to find out patient's functional outcomes. Functional outcome was analyzed between the two groups using Mann-Whitney U test, using SPSS version 21. Result: There was no significant statistical difference between the functional outcome of patients with distal radius fracture treated with across wrist external fixator vs volar buttress plate, in term of QuickDASH score. Furthermore, age and gender also were having no effect on functional outcome in our population. Conclusion: Across wrist external fixator is a reasonable option for AO C2/C3 type fractures of the distal radius with comparable results with volar buttress plate. It is the procedure of choice in high volume tertiary care hospitals like Gurki Trust Teaching hospital as it saves time, have similar functional outcome score, no need to re-open for removal of implant, less chances of tendon rupture as compared to volar buttress plate for distal radius fracture.